Multidisciplinary Predialysis Care in Phra Nakhon Si Ayutthaya Hospital. - ชาวโพนทอง, เสาวลักษณ์ (Journal of Preventive Medicine Association of Thailand, 2019)
A Retrospective case control study was performed in 259 CKD patients who were cared by multidisciplinary care team (MDT) in CKD clinic since 1st October 2014 - 30th September 2015. Annually rate of decline in estimated glomerular filtration rate (eGFR) in mean(SD) is 0.28 4.16 ml/min/1.73 m2/yr in MDT care group. The mean (SD) of annually rate of decline in eGFR in CKD patients with comorbid diabetes in MDT care group showed significantly lower than CKD patients with comorbid diabetes under the usual care process -0.96 4.40 vs -6.11 9.42 ml/min/1.73m2/yr (p=0.003). The rate of unplanned hemodialysis in patients with end stage renal disease was decrease from 23.26% to 8.33% after MDT care. In conclusion: The MDT care in our study is shown that the rate of decline in eGFR is slower than usual care process and decreased rate of unplanned hemodialysis that can improve quality of life and decrease mortality rate.